2012
DOI: 10.1016/j.fob.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization, molecular cloning and extracellular production of a phospholipase A1 from Streptomyces albidoflavus NA297

Abstract: A novel metal ion-independent phospholipase A1 of Streptomyces albidoflavus isolated from Japanese soil has been purified and characterized. The enzyme consists of a 33-residue N-terminal signal secretion sequence and a 269-residue mature protein with a deduced molecular weight of 27,199. Efficient and extracellular production of the recombinant enzyme was successfully achieved using Streptomyces lividans cells and an expression vector. A large amount (25 mg protein, 14.7 kU) of recombinant enzyme with high sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 27 publications
2
35
2
1
Order By: Relevance
“…This catalytic site resembles that of SsEst (1ESC) with a Ser-His dyad and the carbonyl group of Trp280. The active site of PLB 684 may correspond to that of SaPLA 1 , which was previously reported by Sugimori et al [20,33]. Molecular modelling indicated that His73 may stabilize the phosphoric group of the bound phospholipid, thereby imparting the substrate specificity that PLB 684 has towards phospholipids over 4-nitrophenyl esters.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…This catalytic site resembles that of SsEst (1ESC) with a Ser-His dyad and the carbonyl group of Trp280. The active site of PLB 684 may correspond to that of SaPLA 1 , which was previously reported by Sugimori et al [20,33]. Molecular modelling indicated that His73 may stabilize the phosphoric group of the bound phospholipid, thereby imparting the substrate specificity that PLB 684 has towards phospholipids over 4-nitrophenyl esters.…”
Section: Discussionsupporting
confidence: 62%
“…PLB 684 has a much higher turnover rate and somewhat low affinity toward phospholipid, indicating that the formation of the ES may be the rate limiting step. The k cat /K m value (703 mM À1 Ás À1 ) of PLB 684 is higher than that of SaPLA 1 (265 mM À1 Ás À1 ) [20] and is comparable to that of SMC (756 mM À1 Ás À1 ) [43].…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations